2013
DOI: 10.1371/journal.pone.0080782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylcysteine in Ozone-Induced Chronic Obstructive Pulmonary Disease Model

Abstract: IntroductionChronic exposure to high levels of ozone induces emphysema and chronic inflammation in mice. We determined the recovery from ozone-induced injury and whether an antioxidant, N-acetylcysteine (NAC), could prevent or reverse the lung damage.MethodsMice were exposed to ozone (2.5 ppm, 3 hours/12 exposures, over 6 weeks) and studied 24 hours (24h) or 6 weeks (6W) later. Nac (100 mg/kg, intraperitoneally) was administered either before each exposure (preventive) or after completion of exposure (therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 28 publications
2
74
0
Order By: Relevance
“…Treatment of these ozone-exposed mice with MitoQ (5mg/kg intraperitoneally), an antioxidant that targets the mitochondrion, significantly increased mitochondrial membrane potential and decreased the following: ozone-induced airway hyper-responsiveness, bronchoalveolar lavage total cell counts, keratinocyte-derived cytokine levels, mitochondrial ROS levels and cellular ROS levels 226 . In contrast, a similar study with a slightly lower ozone exposure of 2.5 parts per million showed that N-acetylcysteine treatment did not attenuate ozone-induced lung injury in the same mouse model of COPD 235 235. .…”
Section: 1 Pulmonary Diseasesmentioning
confidence: 88%
See 2 more Smart Citations
“…Treatment of these ozone-exposed mice with MitoQ (5mg/kg intraperitoneally), an antioxidant that targets the mitochondrion, significantly increased mitochondrial membrane potential and decreased the following: ozone-induced airway hyper-responsiveness, bronchoalveolar lavage total cell counts, keratinocyte-derived cytokine levels, mitochondrial ROS levels and cellular ROS levels 226 . In contrast, a similar study with a slightly lower ozone exposure of 2.5 parts per million showed that N-acetylcysteine treatment did not attenuate ozone-induced lung injury in the same mouse model of COPD 235 235. .…”
Section: 1 Pulmonary Diseasesmentioning
confidence: 88%
“…. The improvement observed in pulmonary function with MitoQ but not N-acetylcysteine suggests that mitochondrially targeted therapies to be more efficacious and that mitochondrial oxidants play a pivotal role in ozone-induced lung injury 235 .…”
Section: 1 Pulmonary Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Exposure to ozone and particulates, as well as the use of lung proteases have also been used as models of COPD. Chronic (6 week) ozone exposure in mice causes significant lung injury with some features related to inflammatory and emphysematous changes occurring in human COPD as well as changes in lung function and AHR [20,32,33]. Exposure to ultrafine particles, silica, coal dust and diesel exhaust particles (DEP) has been used which all cause significant levels of oxidative stress, inflammation and emphysema [20].…”
Section: Animal Models Of Copdmentioning
confidence: 99%
“…In future, bioinformatic comparisons of signature genes or pathways from clinical specimens from patients with different sub-phenotypes of COPD need to be integrated with clinical observations and similar phenotypic end points as clinical studies and related back to in vivo models in order to further understand, define and treat COPD (Figure 3, [19,39,40]). Only then can animal models be tailored precisely to the specific physiological and pharmacological features of human COPD which each model possesses [6,[17][18][19][20][22][23][24][25]32,33].…”
Section: Animal Models Of Copdmentioning
confidence: 99%